A lepra e a letra: escrita e poder sobre a doença na cidade de Belém (1897-1924) - Gomes, Elane Cristina Rodrigues (2019)
This thesis was guided by the following question: In which way did different writings engage in power relations about the leprosy in the city of Belém between the final of the 19th and the beginning of the 20th centuries? Having as starting point a city erected by the letters, we have analyzed the writing of periodic papers, governmental reports, official letters, legislation, medical articles and the diary of Friar Daniel Rossini Samarate, in the attempt of observing the different perceptions over the disease and the remedial practices. From then, the research was oriented so as to understand how the newspapers built up fears upon the disease which allowed a very faint relation between the isolation and the charity, standing out the tension of the medical practice and the attitudes of a population once rejected and that had undergone various treatments for a disease that, although millennial, provoked restlessness and doubts among the aesculapius. Getting into the routine of the Tucunduba Asylum, by means of the writings of Friar Daniel Samarate, we aimed at approaching the several sociability net in the inside of the asylum, identifying whom were the inmates and their survival dynamics in the leprosarium, emphasizing the narrative of the sickened towards the way of how the leprosy got taking control of the body from the experience of time and pain, revealing by means of the writing of a diary the sensations produced by the disease and their restless attempts of cure.